Ultrasonic extraction of ascorbic acid from indigenous leaves prior to detection by fluorescence spectroscopy - A. Bakar, Nurul Farehah (2018)
Indigenous leaves are kind of vegetables with full of nutritional composition as compared to tropical vegetables, which are rich sources of essential vitamins and also rich in antioxidant. Ascorbic acid (vitamin C) is a well-known function as antioxidant which has the potential to inhibit the oxidative damage in body cells by trapping free radicals. In this study, the concentration of ascorbic acid in indigenous leaves was determined. Samples of indigenous leaves such as tenggek burung (Euodia redlevi), ulam raja (Cosmos Caudatus) and pegaga (Centella asiatica) were extracted by an ultrasonic extraction technique prior to the determination of ascorbic acid by fluorescence spectroscopy. The extraction parameters such as types of solvent, concentration of solvent, time of extraction, temperature of extraction and sample weight were optimized. The samples were extracted utilizing optimum parameters which were 1.4 g of the sample in 0.175 M sulphuric acid at 45 °C for 50 minutes. The result showed the ascorbic acid content for wet samples in tenggek burung, pegaga and ulam raja were 0.0145 mg/g, 0.0237 mg/g and 0.0309 mg/g while for dry samples were 0.0136 mg/g, 0.0214 mg/g and 0.0287 mg/g. It is proven that indigenous leaves were natural sources of ascorbic acid.